Pengembangan Modul Belajar Membaca tanpa di Eja untuk Peserta didik dengan Kesulitan Membaca Sekolah Dasar - Edwar, Ahmad; Adilah, Nida; Permana, Rusma (Attractive : Innovative Education Journal, 2023)
This development research aims to develop a beginning reading learning module for children with grade I learning difficulties and determine the feasibility of the module. This research uses the Borg and Gall development procedure which has been simplified into 4 stages, namely (1) research and data collection, (2) planning, (3) module development, (4) validation and testing. The research subjects were students who had difficulty learning to read at the beginning of grade I elementary school. Data collection techniques use observation, reading ability tests, product validation questionnaires by experts. The steps used in this research and development are (1) research and gathering initial information; (2) planning; (3) product format development; (4) small scale trials; (5) final revision and product improvement. Module validation is carried out by media expert validators, material experts and class teachers. The score from the media expert validator got a percentage of 96%, the score from the media expert validator got a percentage of 96%, the class teacher got a percentage of 100%. Thus, all validation results are classified in the "very feasible" category. Based on research on the quality of learning media, learning modules without spelling using the Montessori method have been made feasible and practical for use in teaching and learning reading activities at MIS Nurul Falah Kemuning. Keywords: Reading Difficulty, Learning Module Development, Students Reading Difficulty